CaWRKY27 Negatively Regulates H2O2-Mediated Thermotolerance in Pepper (Capsicum annuum) - Dang, Fengfeng; Lin, Jinhui; Xue, Baoping; Chen, Yongping; Guan, Deyi; Wang, Yanfeng; He, Shuilin (Frontiers in Plant Science, 2018)
Heat stress, an important and damaging abiotic stress, regulates numerous WRKY transcription factors, but their roles in heat stress responses remain largely unexplored. Here, we show that pepper (Capsicum annuum) CaWRKY27 negatively regulates basal thermotolerance mediated by H2O2 signaling. CaWRKY27 expression increased during heat stress and persisted during recovery. CaWRKY27 overexpression impaired basal thermotolerance in tobacco (Nicotiana tabacum) and Arabidopsis thaliana; CaWRKY27-overexpressing plants had a lower survival rate under heat stress, accompanied by decreased expression of multiple thermotolerance-associated genes. Accordingly, silencing of CaWRKY27 increased basal thermotolerance in pepper plants. Exogenously applied H2O2 induced CaWRKY27 expression and CaWRKY27 overexpression triggered the accumulation of H2O2 in Arabidopsis and pepper leaves, indicating a positive feedback loop between H2O2 accumulation and CaWRKY27 expression. Consistent with this, CaWRKY27 silencing decreased H2O2 accumulation. These changes may result from changes in levels of reactive oxygen species (ROS)-scavenging enzymes, since the heat stress-challenged CaWRKY27-silenced pepper plants had significantly higher expression of multiple genes encoding ROS-scavenging enzymes, such as CaCAT1, CaAPX1, CaAPX2, CaCSD2, and CaSOD1. Therefore, CaWRKY27 acts as a downstream negative regulator of H2O2-mediated heat stress responses, preventing inappropriate responses during heat stress and recovery.